The Influence of Eco-Storytelling and Digital Destination Branding on Tourist Visit Intention to Gunung Salak Village, Tabanan - Dewi, I Gusti Agung Ayu Ana Sintya; Dewi, Luh Komang Candra; Kartimin, I Wayan (LPPM Universitas Dhyana Pura, 2026)
This study aims to analyze the influence of eco-storytelling and digital destination branding on tourist visit intention to Gunung Salak Village, Selemadeg Timur District, Tabanan Regency, Bali. Gunung Salak Village is registered as a pioneer tourism village on the Jadesta platform of the Ministry of Tourism and Creative Economy, yet its digital promotion and ecological narrative communication remain underdeveloped. Using the Stimulus-Organism-Response (S-O-R) theoretical framework, this quantitative research employed a purposive sampling technique with 100 respondents who had knowledge of or interest in Gunung Salak Village as a tourism destination. Data were collected through questionnaires measured using a five-point Likert scale and analyzed through multiple linear regression using SPSS version 26. The results of the study indicate that eco-storytelling has a positive and significant effect on tourist visit intention (t = 4.217; sig. = 0.000), digital destination branding has a positive and significant effect on tourist visit intention (t = 3.894; sig. = 0.000), and both variables simultaneously have a positive and significant effect on tourist visit intention (F = 38.672; sig. = 0.000) with a coefficient of determination (R²) of 0.441, meaning that 44.1% of the variance in tourist visit intention is explained by eco-storytelling and digital destination branding. These findings imply that strengthening ecological narratives and digital destination identity are essential strategies for developing Gunung Salak Village as a competitive and sustainable rural tourism destination.